2017
DOI: 10.22159/ajpcr.2017.v10i2.15722
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Planned Teaching Programme on Knowledge Regarding Cervical Cancer Among Women”.

Abstract: Objectives: To determine the effectiveness of planned teaching programme (PTP) on knowledge regarding cervical cancer among women at selected urban area Karad and to find out the association between knowledge scores with selected sociodemographic variables among women in selected urban areas at Karad. Methods:Evaluative research approach was used for the study and conducted in urban area Koyana Vasahat, Karad, Maharashtra, India, using one group pre-and post-test design. Systematic proportionate sampling techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…There was however statistically significant improvement in the percentage scores between the pre-intervention and post-intervention responses by the students across board. This is an indication of the success of educational intervention strategy used in this study which have also been recorded by some previous studies [21,22]. A possible explanation for this overall improvement in the post-intervention maybe that the students have gained more knowledge of cervical cancer from the intervention lecture in addition to the rudimentary knowledge as health care students.…”
Section: Discussionsupporting
confidence: 83%
“…There was however statistically significant improvement in the percentage scores between the pre-intervention and post-intervention responses by the students across board. This is an indication of the success of educational intervention strategy used in this study which have also been recorded by some previous studies [21,22]. A possible explanation for this overall improvement in the post-intervention maybe that the students have gained more knowledge of cervical cancer from the intervention lecture in addition to the rudimentary knowledge as health care students.…”
Section: Discussionsupporting
confidence: 83%
“…The result of the current research also congruent with Said et al (12) who showed that, there was a highly statistical significant improvement regarding cervical cancer knowledge concerning meaning, types, risks, symptoms, diagnostic and treatment P ≤ 0.001. As well as, the findings agreed with Naregal et al (23) who revealed that there was a significant difference between the two tests was tested using paired t-test the level of significant was highly (p<0.001) indicated that there was a significant difference in the knowledge of women on cervical cancer.…”
Section: Zagazig Nursing Journalsupporting
confidence: 89%
“…Studies related to effectiveness of structured teaching programme shows similar results. Study by Shrikant Desai, 12 Ujwala A Chopade, 13,14 Prakash M Naregal 15,16 and Prabhuswami Hiremath. 17 proved that STP could be an effective mean for improving the knowledge.…”
Section: Discussionmentioning
confidence: 99%